Makna Pesan Komunikasi Iklan Minuman â€œSpriteâ€ dengan Pendekatan Roland Barthes - Munandar, Pramudita (Magister of Communication Science, Sahid University Jakarta., 2021)
One way to introduce a product to the wider community is through advertising. Advertising is needed to continuously inform product features and benefits, create preferences, and remind and place product brands in consumers' minds. many symbols and signs are used to convey messages In an advertising Likewise, in the Sprite advertisement